1995
DOI: 10.1038/376490a0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of serum response factor core bound to DNA

Abstract: The human serum response factor is a transcription factor belonging to the MADS domain protein family with members characterized from the plant and animal kingdoms. The X-ray crystal structure of the serum response factor core in a specific-recognition DNA complex shows that the functions of DNA binding, dimerization and accessory-factor interaction are compactly integrated into a novel protein unit. The intrinsic and induced conformation of the serum response element DNA is the principal DNA feature recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
390
4
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(418 citation statements)
references
References 47 publications
23
390
4
1
Order By: Relevance
“…Blake (41) suggested that evidence for intron-facilitated evolution of a gene might be found by comparing the borders of functional protein domains with the placement of introns. The recent elucidation of the x-ray crystal structure of the SRF MADS box demonstrated a novel DNA-binding motif, a coiled-coil, and a stratified structural subdomain involved in dimerization (2). We showed here ( Fig.…”
Section: Fig 9 Srf Promoter Activity Elevated During Myogenesis Is mentioning
confidence: 52%
See 1 more Smart Citation
“…Blake (41) suggested that evidence for intron-facilitated evolution of a gene might be found by comparing the borders of functional protein domains with the placement of introns. The recent elucidation of the x-ray crystal structure of the SRF MADS box demonstrated a novel DNA-binding motif, a coiled-coil, and a stratified structural subdomain involved in dimerization (2). We showed here ( Fig.…”
Section: Fig 9 Srf Promoter Activity Elevated During Myogenesis Is mentioning
confidence: 52%
“…The structure of the MADS box domain, recently elucidated by Pellegrini et al (2), was assembled before the divergence of plants and animals. The identical MADS box structures were present in yeast transcription factors MCM1 and ARG80, a large number of homeotic like plant proteins, and invertebrate and vertebrate SRFs (reviewed in Ref.…”
mentioning
confidence: 99%
“…The N-terminal DNA-contacting half of the MADS domain forms an amphipathic a-helix that contacts DNA and contributes to the strength of dimerization. The C-terminal half of MADS domain forms a series of anti-parallel b-sheets that function as a dimerization interface (Hassler and Richmond, 2001;Pellegrini et al, 1995;Santelli and Richmond, 2000;Tan and Richmond, 1998). We did not address critical amino acids in the MADS domain in the reverse yeast two-hybrid screens due to the fact that MADS domain-containing versions of AP3 and PI do not interact strongly in yeast two-hybrid assays.…”
Section: Discussionmentioning
confidence: 99%
“…The 56-amino acid MADS domain possesses both DNA-binding and dimerization functions as demonstrated by X-ray structures of the MADS domains of the mammalian proteins SRF and MEF2 and the yeast protein MCM1. The amino terminal end of the MADS domain contacts DNA while the C-terminal end contains two anti-parallel b sheets that function as a dimerization interface (Figure 1) (Hassler and Richmond, 2001;Pellegrini et al, 1995;Santelli and Richmond, 2000;Tan and Richmond, 1998). The 80-amino acid K domain contains several (abcdefg) n heptad repeats in which a and d positions are occupied by hydrophobic amino acids suggesting that K domain forms a series of amphipathic a-helices (Ma et al, 1991;Riechmann and Meyerowitz, 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…Since the NLS and the DNA-binding domain or SRF are spatially distinct, SRF should act well as an adapter between the plasmid DNA and the importin nuclear import machinery. 28,29 In experiments using SRF-expressing CV1 transfectants, we routinely observed decreased nuclear localization of micro-injected plasmids, including the SV40 promoter/enhancer containing pCAT-control. While it is possible that the aberrant expression of SRF caused a down-regulation of general plasmid nuclear import, perhaps by transcriptionally regulating the expression of one or more transcription factors needed for SV40 DNA nuclear import, it is more likely that the decreased nuclear import of the pCAT-control plasmid was due to experimental variation.…”
Section: Discussionmentioning
confidence: 99%